Perancangan Efisiensi Lintasan Produksi dengan Menggunakan Metode Helgeson-Birnie (Ranked Positional Weight) Untuk Meningkatkan Kapasitas Produksi (Studi Kasus Pada Unit Produksi I Shift I PT. SUMBETRI MEGAH) - Wiky Sabardi; Ryan Pramanda; Dewiyana; Diki Suhanda (Fakultas Teknik Universitas Samudra, 2021)
The problem of line balancing in industry, assembling, and manufacturing often occurs. This is indicated by a relatively high bottleneck of work in process at several stations, resulting in non-optimal line efficiency and non-smooth process flow. This study aims to calculate line balancing and determine the division of work stations that can increase production capacity in the production unit I shift I pt. Magnificent resource. This study used the Helgeson-Birnie (Ranked Positional Weight) method. From this research, the design results were obtained with line efficiency (line efficiency) 89.16%, idle time 2730.85, balance delay 10.84%, smoothness index (smoothness index) 781.24, and the number of work stations 15. Based on the calculation, it can be seen that there is an increase in line efficiency from 74.46% to 89.35%, which is 14.89%.